Investigation of Non-Linear Ship Hydroelasticity by CFD-FEM Coupling Method - Zhe Sun; Guang-Jun Liu; Li Zou; Hao Zheng; Kamal Djidjeli (Journal of Marine Science and Engineering, 2021)
With the increase of ship size, the stiffness of the hull structure becomes smaller. This means that the frequency of wave excitation tends to be closer to the natural frequency of the hull vibration, which in turn makes the hydroelastic responses more significant. An accurate assessment of the wave loads and motion responses of hulls is the key to ship design and safety assessment. In this paper, the coupled CFD (Computational Fluid Dynamics)-FEM (Finite Element Method) method is used to investigate the non-linear hydroelasticity effect of a 6750-TEU (Twenty-foot Equivalent Unit) container ship. First, by comparing the heave, pitch, and vertical bending moment at midship section (VBM4) against experimental results reported in the literature, the validity of the numerical method in this paper is illustrated. Secondly, the ship responses under different wave length–ship length ratio, wave frequency-structure natural frequency, wave steepness, and ship speeds are studied. It is found that the wave length–ship length ratio has a more important influence on the hydroelastic response than that from wave frequency-structure natural frequency ratio, and the effect of wave non-linearity will behave differently under different wave length–ship length ratio. The increase of rigid body motion caused by forward speed will not correspondingly increase the non-linearity of the hydroelastic response.